End-of-waste criteria for construction & demolition waste - Hjelmar, Ole; Hansen, Jette Bjerre; Wahlström, Margareta; Wik, Ola (TemaNord, 2016)
This report presents the situation within the Nordic countries with respect to production and recycling of construction and demolition waste, in particular crushed concrete, in the form of aggregates, and discusses the conditions and requirements relating to environmental impacts for a possible application of the End-of-Waste option in the Waste Framework Directive. If this option is applied, the material may become a product and it will no longer be regulated by waste legislation. Regulation of crushed concrete under product legislation presents a number of challenges, particularly with respect to environmental protection. The report presents and proposes a methodology for the setting of leaching and risk-based criteria to be fulfilled by crushed concrete (and other waste aggregates) in order to obtain End-of-Waste status. It is further recommended to set impact-reducing conditions on the use of materials obtaining End-of-Waste criteria, and not to allow free use. It should be noted that the work described in this report was carried out during the period from 2010 to 2012.